Malacuik Marapulai Tradition from the Perspective of 'Urf': Case Study of Korong Tiram Nagari Tapakih Sub-District Ulakan Tapakis District Padang Pariaman - Rahma, Fataqia; Azwar, Zainal (Minhaj: Jurnal Ilmu Syariah, 2024)
This research stems from the large number of Padang Pariaman people who carry out the malacuik marapulai tradition. Thus in this study the author explains how the implementation of the malacuik marapulai tradition in Korong Tiram Nagari Tapakih, Ulakan Tapakis District, Padang Pariaman Regency and how Urf views related to this tradition. This type of research uses a descriptive method with a qualitative approach so that it can directly know the implementation of the tradition. While in the research data collection is done by means of observation, interviews and documentation obtained directly from sources related to the research, in this case the informants consist of religious leaders, traditional leaders, and some Padang Pariaman people who have carried out this bajapuik tradition. The results showed that the tradition in malacuik aims to provide provision to prospective brides so that they are able to carry out their responsibilities well as a man, who is considered the leader of the family, this malacuik marapulai tradition has more benefits than its disadvantages. So based on the rules of fiqh, the tradition may be carried out because it will bring a good thing in social life